WATER LEVELS DEPLETION IN SUBSTRATE IN THE DEVELOPMENT OF Heliconia psittacorum L. F. CV. RED OPAL - Gervásio, Eliezer Santurbano; Ishikawa, Francine Hiromi; da Silva, Vanderléia Dias; de Melo Júnior, Júlio César Ferreira (IRRIGA, 2017)
WATER LEVELS DEPLETION IN SUBSTRATE IN THE DEVELOPMENT OF Heliconia psittacorum L. F. CV. RED OPAL ELIEZER SANTURBANO GERVÁSIO1; FRANCINE HIROMI ISHIKAWA1; VANDERLÉIA DIAS DA SILVA2 E JULIO CÉSAR FERREIRA DE MELO JUNIOR1 1 Professores do Colegiado de Engenharia Agronômica da UNIVASF (campus Ciências Agrárias, Rodovia BR 407, km 119, CEP: 56300-000, Petrolina – PE) email: eliezer.gervasio@univasf.edu.br; francine.hiromi@univasf.edu.br; julio.melo@univasf.edu.br; 2 Mestre em Agronomia pela UNEB (Rua Edgar Chastinet, s/n - São Geraldo, Juazeiro - BA, CEP: 48905-680) email: vanderleia.dias@hotmail.com 1 ABSTRACT Flowers and ornamental plants cultivation in Brazil has grown over the years as economic activity. Pernambuco state is one of the major producers and exporters of Heliconia sp, a highlighting tropical flower in Brazil. However, detailed information regarding to the irrigation needed especially in semiarid conditions remain little studied. The objective was to evaluate different levels of water depletion in the substrate as indicators of irrigation time and its effects on growth and productivity of Heliconia psittacorum L.f. cv. Red Opal in pots. The experiment was conducted in a greenhouse covered with 50% shade cloth located at Campus of Agricultural Sciences at Federal University of Vale do São Francisco in Petrolina, PE, Brazil. This is a semiarid region in Brazil where the irrigation is necessary for production of most crops. The experimental design was completely randomized blocks with six levels of water depletion in the substrate and five replications. The determination of the depletion level was performed by use of weighing lysimeters. The following parameters were evaluated: the water consumption of the plants, the amount of macro and micronutrients applied and the number of tillers. It was concluded that the water depletion level at 5% on the weight capacity of container increased the number of tillers. However, the management under conditions of free growth of tillers inhibited the emission of flower stalks of Heliconia grown in pots. The efficient water use in semiarid climate is a requirement for the sustainability and reduction of production costs. Keywords: tropical flowers, irrigation, intensive farming, lysimeters GERVÁSIO, E.S.; ISHIKAWA, F.H.; SILVA, V.D.; MELO JÚNIOR, J.C.F. EFFECT OF WATER LEVELS DEPLETION IN SUBSTRATE IN THE DEVELOPMENT OF Heliconia psittacorum L. F. CV. RED OPAL GROWN IN POTS 2 RESUMO O cultivo de flores e plantas ornamentais no Brasil como atividade econômica tem crescido ao longo dos anos. O estado de Pernambuco é um dos principais produtores e exportadores de Heliconia sp, flor tropical que tem se destacado no Brasil. No entanto, informações detalhadas sobre a irrigação necessária, especialmente em condições semiáridas, ainda foi pouco estudada. O objetivo do presente trabalho foi avaliar diferentes níveis de depleção de água no substrato como indicadores de tempo de irrigação e seus efeitos sobre o crescimento e produtividade de Heliconia psittacorum L.f. cv. Red Opal cultivadas em vasos. O experimento foi conduzido em casa de vegetação revestida com tela de sombreamento de 50%, localizada no Campus de Ciências Agrárias da Universidade Federal do Vale do São Francisco, em Petrolina, PE, Brasil. Esta é uma região semiárida, onde a irrigação é necessária para a produção da maioria das culturas. O delineamento experimental foi inteiramente casualizado, com seis níveis de depleção de água no substrato e cinco repetições. A determinação do nível de depleção foi realizada por meio da utilização de lisímetros de pesagem. Foram avaliados os seguintes parâmetros: consumo de água das plantas, a quantidade de macro e micronutrientes aplicados e o número de perfilhos emitidos. Concluiu-se que o nível de depleção de água no substrato de 5% em relação à capacidade de container permitiu o aumento do número de perfilhos. No entanto, o manejo da cultura sob condições de livre crescimento de perfilhos inibiu a emissão de hastes florais dessa cultivar, quando cultivada em vaso. O uso eficiente da água em clima semiárido é um requisito para a sustentabilidade e redução do custo de produção. Palavras-chave: flores tropicais, irrigação, cultivo intensivo, lisímetro